2004
DOI: 10.1097/00006199-200405000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Sexual Intercourse and Condom Use Intentions Among Spanish-Dominant Latino Youth

Abstract: This study represents initial efforts to address the needs of Spanish-dominant Latino youth. The identification of salient beliefs that may predict sexual risk and protective behavior are relevant to the design of culturally and linguistically effective interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
103
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 136 publications
(118 citation statements)
references
References 23 publications
11
103
1
3
Order By: Relevance
“…Measures used in the adolescent questionnaire were based on previous research with inner-city adolescents, including Latino and Spanish-speaking youth 13 to 18 years of age (Jemmott, Jemmott, & Fong 1992Villarruel, Jemmott, Jemmott, & Ronis, 2004). Most of the adolescent measures were previously translated into Spanish (Villarruel, et al, 2004).…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measures used in the adolescent questionnaire were based on previous research with inner-city adolescents, including Latino and Spanish-speaking youth 13 to 18 years of age (Jemmott, Jemmott, & Fong 1992Villarruel, Jemmott, Jemmott, & Ronis, 2004). Most of the adolescent measures were previously translated into Spanish (Villarruel, et al, 2004).…”
Section: Instrumentsmentioning
confidence: 99%
“…Most of the adolescent measures were previously translated into Spanish (Villarruel, et al, 2004). Similar procedures based on the method of decentering (Werner & Campbell, 1970) were used to translate new items for this study.…”
Section: Instrumentsmentioning
confidence: 99%
“…In summary, findings from five studies supported that adolescents' intentions to have sex and condom use are predictors of protected intercourse (Buhi & Goodson, 2007;Koniak-Griffin et al, 2003;Koniak-Griffin & Stein, 2006;Prado et al, 2009;Villarruel et al, 2004). Findings from four studies indicated positive relationships between adolescents' perceptions of normative beliefs or subjective norms about condom use and engagement in intercourse and adolescents' intentions to use condoms (Koniak-Griffin et al, 2003;Koniak-Griffin & Stein, 2006;Villarruel et al, 2004) and adolescents' sexual activity (Buhi & Goodson, 2007).…”
Section: Relationship Between Adolescents' Attitudes Subjective Normmentioning
confidence: 82%
“…Villarruel, Jemmott, Jemmott, and Ronis (2004) conducted a study in Philadelphia and included 141 Latino adolescents between 12 and 18 years old. Results indicated positive correlations between adolescents' self-reported intentions to have intercourse in the next 3 months and adolescents' favorable attitudes and perceptions of approval of subjective norms regarding engagement in intercourse.…”
Section: Relationship Between Adolescents' Attitudes Subjective Normmentioning
confidence: 99%
See 1 more Smart Citation